OBAT KUMUR EKSTRAK ETANOL KULIT BATANG KAYU MANIS (CINNAMOMUM VERUM J.PRESL) SEBAGAI PENGHAMBATAN PERTUMBUHAN BAKTERI STREPTOCOCCUS MUTANS - Umayah, Dani Yatul; Nawangsari, Desy; Fitriana, Adita Silvia (Sekolah Tinggi Ilmu Keperawatan Muhammadiyah Pontianak, 2024)
Bad breath is caused by volatile sulfur compounds (VSCs) produced by the anaerobic bacteria Streptococcus mutans through the decomposition of food waste. This problem can be overcome with antibacterial mouthwash. Cinnamon contains essential oils, phenols, flavonoids, saponins and terpenoids, which have antibacterial properties. This study aimed to formulate a mouthwash from ethanol extract of cinnamon and evaluate its physical properties, stability, and inhibitory power against Streptococcus mutans using the Kirby-Bauer method. This research was experimental by making mouthwash using cinnamon extract with concentrations of 10% (FI), 12.5% ​​(FII), and 15% (FIII). The results of the research showed that the mouthwash preparations were brick red in color with different intensities, all preparations were homogeneous, had a pH according to standards except for FII and all preparations did not meet the required viscosity values. The stability test showed that the preparation was stable in storage except for the viscosity parameter FIII. The results of the antibacterial activity test showed that the inhibitory power of FI, FII, FIII against Streptococcus mutans bacteria was 7.33 mm, 8.50 mm, 9.33 mm respectively. The inhibitory power of FII and FIII was better than the positive control, namely total care-antibacterial mouthwash (8.33 mm).